STUDYING THE COMPOSITION OF HIGH-WATER PLANTS AND DETERMINING THE EFFECTIVENESS OF USING RAW MATERIALS (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
In recent years, the country has been consistent with the conservation of medicinal plants, the use of natural resources wisely, the establishment and recycling of plantations for medicinal plants reforms are being implemented.